PERBEDAAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN MENGGUNAKAN TEKNIK OUTLINE (KERANGKA KARANGAN) SISWA KELAS V SD NEGERI 161 PEKANBARU - Desi Permata Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research was motivated by the low narrative essay writing skills of fifth class students in 161 Public Elementary Schools in Pekanbaru. That is because in Indonesian languange learning, the teacher has feel difficult to finding the right learning method or technique in delivering narrative essay writing material. Based on the above problems, the problem statement is obtained “ whether there are narrative essay writting skills of control class students and experimenttal classes in narrative essay writing skills of control class students and experimental classes with learning using in class. This research used method of quasy-eksperimental non equivalent control group design. This research carried in two fifth classes of 161 public elementary schools in pekanbaru, namely fifth A class as control and fifth B class as experimental class, with each class has 30 sudents. Based on the posttest results, it was found that the average narrative essay writing skills for students with outline techniques (experimental framework) were higher than the average narrative essay writing skills for students who did not use the outline technique or using conventional learning. After taking action on two classes, the average posttest of the experimental class has a gain average of 0,45 for the moderate category, which means there is an increase above the average and the control class has the average gain is 0,12 or the low category, which means an increase below the average. This proves that the outline technique (essay framework) can further improve students' narrative essay writing skills compared to without outline techniques (essay framework) in fifth grade students in 161 Pekanbaru Public Elementary School.